Regulation of the Duration of Spawning Cycles of Catfish in Industrial Aquaculture - Romanova , Elena; Lyubomirova, Vaselina; Romanov, Vasily; Shadyeva, Ludmila; Shlenkina, Tatiana (KnE Life Sciences, 2021)
This article is devoted to the study of the qualitative and quantitative characteristics of the African Catfish Clarias gariepinus eggs produced at different durations of the inter-spawning interval. Eggs were produced artificially using sex hormones. In industrial aquaculture, the African Catfish Clarias gariepinus does not reproduce naturally. Therefore, the problem of obtaining high-quality eggs that will be used for in-vitro fertilization is urgent. To implement artificial spawning of fish in industrial aquaculture, it is necessary to correctly choose the effective hormonal stimulator and empirically select its dose. Sex hormones are involved in regulating the duration of the inter-spawning interval and affect the quality of eggs produced both for fertilization and for food purposes. The pituitary gland of the African Catfish Clarias gariepinus and surfagon were used as gametogenesis stimulators. The aim of the work was to study the optimal duration of the inter-spawning interval and the effect of hormonal inducers used to stimulate artificial spawning in industrial aquaculture. The use of the catfish pituitary gland in fresh or acetonated form as a hormonal stimulator provided higher-quality eggs, compared to the synthetic hormonal drug - surfagon. Stimulation with acetonated pituitary injections reduced the inter-spawning interval of the African Catfish Clarias gariepinus to three months, and the use of surfagon prolonged the inter-spawning interval to four months. Reducing the duration of the inter-spawning interval is important for the production of the African Catfish Clarias gariepinus eggs for food purposes. Studies have shown that reducing the optimal duration of the inter-spawning interval negatively affects the quality of the produced eggs and their quantity. This research was financially supported by a grant from the Russian Foundation for Fundamental Research, project No. 18-016-00127. Keywords: aquaculture, African Catfish Clarias gariepinus, eggs, inter-spawning period, sex hormones, oocytes